Echocardiography with Strain Assessment in Psychiatric Diseases: A Narrative Review - Aleksandra Spyra; Aleksandra Sierpińska; Alexander Suchodolski; Szymon Florek; Mariola Szulik (Diagnostics)
Mental disorders (MDs) are among the major causes of morbidity and mortality worldwide. Individuals with severe MDs have a shorter life expectancy, primarily due to cardiovascular diseases. Echocardiography facilitates the evaluation of alterations in cardiac morphology and function, resulting from various cardiac pathologies. The aim of this review was to explore the current evidence base behind the myocardial deformation observed in echocardiography in patients with MDs. We primarily focused on the data regarding speckle tracking echocardiography. PubMed, using medical subject headings, was searched to identify studies on this topic. The collected data demonstrated changes in myocardial function in schizophrenia, bipolar disorder, depression, anxiety disorder, stressor-related disorder, post-traumatic stress disorder, eating disorders, sleep–wake disorders, substance-related and addictive disorders, neurocognitive disorders, and borderline personality disorder. The recurrent findings included impaired Left Ventricular Ejection Fraction and Left Ventricular Hypertrophy. Global Longitudinal Strain was significantly altered in patients with anorexia nervosa, bipolar disorder, and substance-related disorders. All reported studies support the consideration of cardiology consultations and a multidisciplinary approach in the care of patients with MDs with suspected cardiac dysfunction. Further investigation is warranted to determine the significance and prognostic value of myocardial deformation and strain measurements among individuals with MDs, focusing on the value of early detection, especially in asymptomatic cases.